Enhancing Socio-Economic Dynamics: Assessing Regional Governance and Mining Community Benefits post Law Number 3 of 2020 in North Maluku - Hasyim, Hasyim; Syafri, Wirman; Nurdin, Nurliah; Achmad, Mansyur (Universitas Muhammadiyah Ponorogo, 2024)
Mining potential in Maluku Province is the largest contributor to nickel mining in Indonesia with nickel reserves of 39% and copper of 92.48% of the national total. Even though nickel and copper are potential resources in this region, they do not yet have production results that have added value and are highly competitive. Now various investors from China are investing in North Maluku with the above potential mining resources. In fact, China is now interested in building a nickel factory in North Maluku, specifically in North Halmahera. The issuance of Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining is a transformation of mineral and coal policy relating to the management and utilization of mineral and coal in Indonesia. The consequence of the amendment to Law Number 4 of 2009, namely the elimination of regional government authority over the management of mineral and coal mining, was taken over by the central government, which applies nationally. The method used in this research is the Hybrid Method as an applied method. The limitation of this research is that it does not technically examine the ecological, economic and social modeling of mining studies in North Maluku. The recommendation of this research is that further in-depth review is needed from a legal, social, ecological and economic perspective to map and review Law No. 3 of 2020, the formation of a cross-sectoral task force to monitor the impact of the implementation of Law No. 3 of 2020 on the environmental and social sectors. and economics.